Trauma Heart and great vessels - Estable, Héctor (Cirugía del Uruguay, 1990)
The appearance in modern society of vehicles of high speed and its irresponsible use; the Asociation with problems especially of social order (alcoholism, crime, unemployment, etc.) that carry to violence in all its expressions, with its high casualty rate has increased in recent years the incidence of injuries and polytraumatized serious.